OPTIMALISASI PEMANFAATAN PLATFORM DIGITAL DALAM UPAYA PENINGKATAN PENJUALAN PRODUK UMKM (STUDI KASUS DESA CIBOGO) - Sony Hartono; Riani Budiarsih; Glisina Dwinoor Rembulan (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The use of digital platforms as a marketing tool is currently not being utilized optimally by MSME actors. This study aims to see how efforts are made to optimize digital platforms in order to expand the marketing of MSME products. This research uses a qualitative approach with a case study method in Cibogo Village, Cisauk District, Tangerang Regency. The results of this study indicate that in general the utilization of digital platforms is not optimal. The intensity of using digital platforms varies in the categories of pre-adoption, beginner and advanced MSME actors. Determining a digital platform that suits the type of business and market segment characteristics is crucial to starting digital marketing. Management of good customer feedback, consistent and regular updating of content or product showcases shows that the business is still active and convinces customers to make transactions. In addition, most MSMEs have not optimized all the features available on digital platforms. Therefore, it is necessary to carry out more intensive training and assistance related to digital marketing literacy adapted to the characteristics of the Cibogo Village MSME actors.